Osteochondroses. Issue 6 (December 2016) - Brewer, Paul; Fernandes, James A.
Abstract: Osteochondrosis is an umbrella term for a broad variety of conditions affecting all areas of the body. The aetiology is not fully understood and the clinical effects vary from mild pain and discomfort to gross disability. Generally they are self-limiting conditions and can be managed with activity modification and physical therapy. However, some conditions, such as Legg–Calve–Perthes, or Blount's, can result in lifelong disability if left untreated. This paper aims to give a broad overview of the osteochondroses and present a synopsis of the more common types, reviewing the current literature and giving guidance on management.